Wolność działalności gospodarczej — rozważania na kanwie sprawy „drukarza z Łodzi” - Kaczan, Damian Rafał (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The article is devoted to the issue of freedom of economic activity in Polish law. The analysis focuses on the considerations of the Constitutional Tribunal, Supreme Court and common courts related to the “printer from Łódź” case, which has been the subject of lively public debate recently. Introductory remarks include the assessment of the importance of the freedom of economic activity for the modern liberal state and the risks associated with full market liberalization. The main remarks are divided into five parts. The first part is devoted to constitutional regulations, in particular to the leading role of freedom of economic activity among the elements of the social market economy (the model on which the economic system of the Republic of Poland is based). Premises for the admissibility of restrictions on this freedom are also indicated. The second part distinguishes two freedoms of economic activity — in formal and material terms. It states that due to the specificity of each of them, any restrictions should be primarily of public or private law, respectively. The third part presents the facts and court’s statements regarding the “printer from Łódź” case. According to the courts, the mere conduct of economic activity obliges the entrepreneur and his employees to provide benefit to anyone interested in goods or services provided by the entrepreneur.The correctness of the above conclusion is analyzed in the fourth part. Basically, it has been criticized. Its rejection in relation to entrepreneurs is supported by: the contradiction of the above order with the essence of constitutional freedom of economic activity and the limited scope of statutory and EU provisions on anti-discrimination function. However, it is pointed out that this obligation lies with some entrepreneurs — for example, professionals operating on the pharmaceutical market and compulsory insurance market, as well as entities with a dominant position on the relevant market, provided that their refusal to perform the service is an abuse of this position. As for the employees of entrepreneurs, it is emphasized that they are not related to the employer’s clients by legal relations, including the obligation to fulfill the benefit. It is noticed that they may have an obligation to perform certain activities for the employer’s contractors, but it results from legal relations between them and the entrepreneur. The fifth part concerns the judgment of the Constitutional Tribunal declaring the provision of the Code of Petty Offences applied in the case of a “printer from Łódź” as inconsistent with the constitutional principle of proportionality. The author approves the Tribunal’s statement that the legislator should introduce criminal sanctions only as a last resort, if it is impossible to achieve the assumed goals in a different way. However, he criticized the thesis that the analyzed code provision could have constituted an independent legal basis for the obligation to fulfill the benefit due to its alleged anti-discrimination function.The article ends with conclusions. The general direction of regulation of the freedom of economic activity in Polish law is assessed positively by the author. However, he does not exclude that in some areas of activity the legislator deserves criticism — for example due to the introduction of the so-called “pharmacy for pharmacist” Act. He also denied the admissibility of a broad interpretation of the rules restricting freedom of economic activity.
Keywords: freedom of economic activity; entrepreneur; discrimination; freedom of contract